Low Formaldehyde Binders for Mineral Wool Insulation: A Review. Issue 4 (12th January 2022) - Bennett, Thomas M.; Allan, John F.; Garden, Jennifer A.; Shaver, Michael P.
Abstract: Insulating materials are ubiquitous in a built environment and play a critical role in reducing the energy consumed to maintain habitable indoor environments. Mineral wool insulation (MWI) products, including glass, stone, and slag variants, are the most widely used class of insulating materials in Europe and account for more than 50% of the total market by volume. MWI typically consists of two key components: a mesh of inorganic fibers that are several micrometers in diameter, and an organic thermosetting adhesive commonly referred to as the "binder." Traditional phenol‐formaldehyde‐urea (PFU) binders used in the manufacture of MWI are increasingly being scrutinized for the formaldehyde released during their manufacture and service lifetime. The recent classification of formaldehyde as a carcinogen by various safety organizations has accelerated a paradigm shift within the industry toward alternative binder technologies that minimize or indeed eliminate formaldehyde emissions. This review examines more recent strategies for achieving low‐ or zero‐added formaldehyde binders for MWI, with a particular focus on the patent literature. The chemistry underpinning traditional PFU binders is presented and compared to new strategies involving scavenging molecules that decrease formaldehyde emissions, as well as zero‐added formaldehyde binder technologies such as polyester, Maillard, and epoxide thermosets. Abstract : Traditional phenol‐formaldehyde‐urea binders used in mineral wool insulation products release formaldehyde during their manufacture and service lifetime. This review examines recent strategies for achieving low‐ or zero‐formaldehyde binders, such as through the use of scavenging molecules that decrease formaldehyde emissions, as well as formaldehyde free binders including polyester, Maillard, and epoxide thermosets.